The Impact of the Negative Deposit Facility Rate on the Banking System - El Zein, Samer Ajour; Coni, Francesca; Gheshmi, Reza (International Journal of Criminology and Sociology, 2022)
The main aim of the study is to investigate the repercussions of the monetary policy of negative interest rates conducted by the European Central Bank as a response to defective performance levels across the banking system during a time of economic trough afflicting European countries. The assumption under negative interest rates is that this should make monetary institutions more likely to issue credit, thus fighting loan contraction and creating a solid ground for proper money circulation and economic expansion. Simultaneously, this policy entails, for financial institutions, an extra payment due to their liquidity holdings at the ECB, in the form of deposits or current accounts. Nonetheless, it should be kept in mind, that the primary objective of the ECB is to seek price stability, and for this reason, in comparison, the lucrative purpose of the banking sector is a problem to put on the back burner. Under these circumstances, the amount of total payments carried out by the banking system of each 19 countries of the Monetary Union has been the object of the study to understand which countries are more or less sensitive to the policy. Furthermore, those figures are compared to the due forecasted payments to be done by each country's banking system on aggregate level after the recent implementation of a two-tier system for the liquidity held in the current accounts. The results show that a great disproportion exists in the affliction of negative interest rates across the banking system in different eurozone countries and that each of them will be differently affected by the two-tier system.